Antithrombotic therapy in patients with non-traumatic intracerebral haemorrhage and atrial fibrillation: A retrospective study. Issue 1 (January 2020) - Budinčević, Hrvoje; Črnac Žuna, Petra; Saleh, Christian; Lange, Nicholas; Piechowski-Jozwiak, Bartlomiej; Bielen, Ivan; Demarin, Vida
Abstract: Introduction: The aim of the study was to determine the outcome, prescribed therapy, and localization of non-traumatic intracerebral haemorrhage in patients with atrial fibrillation. Patients and methods: This retrospective study enrolled patients with atrial fibrillation hospitalised for non-traumatic intracerebral haemorrhage from 2004 to 2013. We compared the patients according to previous antithrombotic therapy, demographics, previous CHADS2 score, comorbidities, the international normalised ration, localisation of intracerebral hamorrhage, stroke severity, prescribed antithrombotic therapy and outcome. Results: A total of 85 patients were enrolled and assigned to an AT+ group (n = 49; 14 on aspirin, 35 on warfarin) and an AT- group (n = 36; without antithrombotic therapy prior to hospitalisation). The latter had a lower proportion of known atrial fibrillation (90% vs 47%, P < 0.001). The mean INR was 2.6 ± 1.5. The in-hospital mortality rates in both groups were high: 43% in AT+ group and 47% in AT- group. There were no significant differences in any of the predefined comparisons. Conclusion: Treating patients with intracerebral haemorrhage and atrial fibrillation is challenging due to higher mortality rates and issues regarding the use of antithrombotic treatment in stroke prevention. Based on our data, prior antithrombotic therapy was not associated with increased in-hospital mortality rates or poorer functional outcome at hospital discharge in comparison with no prior antithrombotic therapy. Abstract : Cardiology; Clinical research; Emergency medicine; Neurology; Pharmacology; Intracerebral haemorrhage, Atrial fibrillation, Antithrombotic therapy.